Sperm characteristics in a sample of healthy adolescents in São Paulo, Brazil Características de espermatozóides de um grupo de adolescentes saudáveis em São Paulo, Brasil - Marcos Mitsuyoshi Mori; Agnaldo Pereira Cedenho; Sergio Koifman; Miguel Srougi (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2002)
The article presents preliminary data from a prospective investigation in a sample of healthy 14-17-year-old students from a technical school in Sao Paulo, Brazil. Ninety-six Tanner stage 5 and thirty-one Tanner stage 4 adolescents were evaluated: testicular volume was measured using a Prader orchidometer, and semen analysis was performed according to standard procedures. Median testicular volume was 20.0ml among Tanner 5 students and 15.0ml in Tanner 4 students in both the right and left testes. No significant differences were found in sperm volume or motility. Median concentration was 66.0 million/ml for Tanner 5 and 47.0 million/ml for Tanner 4 subjects. Morphological patterns showed abnormal forms in 81.9% of Tanner 5 and 93.6% of Tanner 4 adolescents. Oligospermia (sperm concentration < 5 million/ml) was observed in 7.3% of Tanner stage 5 and 12.9% of Tanner stage 4 individuals. Azoospermia was observed in 3 students (1.8%), with counts less than 1.0 in 8 students (4.8%). The authors discuss the observed results, analyzing the potential implications arising from biological development and potential environmental exposures. O artigo apresenta dados preliminares de um estudo prospectivo com uma amostra de alunos saudáveis variando de idade entre 14 e 17 anos, de uma escola técnica em São Paulo. Foram avaliados 96 adolescentes estágio Tanner 5 e 31 estágio Tanner 4: o volume testicular foi medido utilizando um orquidômetro de Prader, e o espermograma foi realizado de acordo com os procedimentos padronizados. O volume testicular mediano, tanto direito quanto esquerdo, era 20,0ml nos alunos Tanner 5 e 15,0ml nos alunos Tanner 4. Não foram constatadas diferenças significativas no volume ou motilidade espermática. A concentração mediana era 66,0 milhões/ml para Tanner 5 e 47,0 milhões/ml para Tanner 4. Os padrões morfológicos evidenciaram formas anormais em 81,9% dos adolescentes Tanner 5 e 93,6% dos Tanner 4. A oligospermia (concentração espermática < 5 milhões/ml) foi observada em 7,3% dos indivíduos Tanner 5 e 12,9% dos Tanner 4. A azoospermia foi observada em 3 alunos (1,8%), além de uma contagem abaixo de 1,0 em 8 alunos (4,8%). Os autores discutem os resultados observados, analisando as implicações para o desenvolvimento biológico a partir de possíveis exposições ambientais.